2018
DOI: 10.1111/1556-4029.13820
|View full text |Cite
|
Sign up to set email alerts
|

An Evidence‐based Forensic Taxonomy of Windows Phone Dating Apps

Abstract: Advances in technologies including development of smartphone features have contributed to the growth of mobile applications, including dating apps. However, online dating services can be misused. To support law enforcement investigations, a forensic taxonomy that provides a systematic classification of forensic artifacts from Windows Phone 8 (WP8) dating apps is presented in this study. The taxonomy has three categories, namely: Apps Categories, Artifacts Categories, and Data Partition Categories. This taxonom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…The amount of literature focused on discovering forensic artifacts from both mobile dating apps and apps in general has grown gradually ( Cahyani et al, 2019;Gurugubelli et al, 2015;Shetty et al, 2020 ), although it pales in comparison to other areas of mobile forensics ( Anglano et al, 2020;Barmpatsalou et al, 2018 ;Kim and Lee, 2020 ;Zhang and Choo, 2020 ). Atkinson et al (2018) demonstrated how mobile apps could broadcast personal information through wireless networks despite the encryption standards implemented by apps, such as Grindr (a popular dating app).…”
Section: Related Literaturementioning
confidence: 99%
“…The amount of literature focused on discovering forensic artifacts from both mobile dating apps and apps in general has grown gradually ( Cahyani et al, 2019;Gurugubelli et al, 2015;Shetty et al, 2020 ), although it pales in comparison to other areas of mobile forensics ( Anglano et al, 2020;Barmpatsalou et al, 2018 ;Kim and Lee, 2020 ;Zhang and Choo, 2020 ). Atkinson et al (2018) demonstrated how mobile apps could broadcast personal information through wireless networks despite the encryption standards implemented by apps, such as Grindr (a popular dating app).…”
Section: Related Literaturementioning
confidence: 99%
“…By increasing the specificity of a taxonomy, the efficiency of investigating a particular type of application might be significantly improved. For example, Cahyani, Choo, Rahman, and Ashman (2018) developed a forensic taxonomy for the systematic classification of forensic artifacts of Windows Mobile 8 dating apps. The artifact categories of this taxonomy cover timestamps, exchanged messages, matching information, location, and user, partner, and app information.…”
Section: Knowledge Organization Systems In Digital Forensicsmentioning
confidence: 99%